Incidente of phlebitis at Orinoquia Regional Hospital, Casanare-Colombia, 2015-2021 - Castañeda-Porras, Oneida (2024)
Objective. To determine the incidence of phlebitis in the Regional Hospital of Orinoquia during the period 2015-2021. Methods. Cross-sectional descriptive study with records reported to the Adverse Events Information System (SIAVE), after filtering according to eligibility criteria. Subgroup analysis with Epi-Info™ 7.2.4.0 using descriptive statistics, frequency measures, trend/dispersion. Results. Records object of analysis were 840/920(91.3%). The most affected, by affiliation regime: 557(66.3%) subsidized, 199(23.7%) contributory; 467(55.60%) men. Per year, more in 2019(172;20.5%), 2020(140;16.7%), 2021(176;20.9%). By age, average 53 ± 23 years; 85.0%(714/840) were 27 or older. By hospital service: 434(51.1%) hospitalization, 192(22.9%) observation, on average at 12 ± 6 hours. By affected site: 521(62.0%) arm, 134(16.0%) forearm, 88(10.5%) hand, and 9(1.1%) foot; By signs/symptoms: 472(56.2%) redness, 421(50.1%) heat, 271(32.3%) edema, 215(25.6%) pain; events due to change of venipuncture site, 832(99.0%). By risk classification: 755(89.9%) none, 66(7.9%) medium and 9(1.1%) high. Conclusions. The highest incidence of phlebitis occurred in 2021; often the most affected were men under observation in the emergency room or hospitalized and the most affected anatomical site being the arm due to change of venipuncture site at moments around shift change times. It is recommended to generate preventive, education and surveillance actions during hospital care.